Electric Power Quality - Chattopadhyay, Surajit; Mitra, Madhuchhanda; Sengupta, Samarjit (Power Systems, 2011)
In the present day deregulated power market electric power quality issues have become great concerns of utilities, end users and manufacturers. Worldwide researches are going on to address those issues. Electric Power Quality has evolved from the researches carried out by the authors.